Predictors of prodromal Parkinson’s disease in young adult Pink1−/− rats - Lechner, Sarah A.; Welsch, Jacob M.; Pahapill, Natalie K.; Kaldenberg, Taylor A. R.; Regenbaum, Amy; Kelm-Nelson, Cynthia A. (Frontiers in Behavioral Neuroscience, 2022)
Parkinson disease (PD) is a progressive, degenerative disease that affects nearly 10 million people worldwide. Hallmark limb motor signs and dopamine depletion have been well studied; however, few studies evaluating early-stage, prodromal biology exist. Pink1-/- rats, a rodent model of PD mitochondrial dysfunction, exhibit early-stage behavioral deficits, including vocal communication and anxiety, that progress during mid-to-late adulthood (6-12 months of age). Yet, the biological pathways and mechanisms that lead to the prodromal dysfunction are not well understood. This study investigated the Pink1-/- rat in young adulthood (2 months of age). Mixed sex groups of Pink1-/- rats and wildtype (WT) controls were assayed for limb motor, anxiety, and vocal motor behaviors. A customized NanoString CodeSet, based on genetic work in later adulthood, was used to probe for the up regulation of genes involved in disease pathways and inflammation within the brainstem and vocal fold muscle. In summary, the data show that sex differences are consistent with previous work that demonstrate a difference in phenotype in the Pink1-/- model. Key genes identified in this study may be early predictors of PD pathology in the Pink1-/- rat and serve as targets for future drug therapy studies.